The influence of risk and resilience factors on the life satisfaction of adolescents - Botha, Anja (University of the Free State, 2014)
The current South African adolescent cohort grew up in a decade of sociopolitical transformation, a period which has been accompanied by inevitable and continuous instability in the economic, education and health system especially. In general, South Africans are confronted with high levels of trauma exposure due to crime and violence, family dissolution, domestic abuse, accidents, illness and injury. Young adolescents, however, are further confronted with developmental changes in every area of functioning. In fact, early adolescence is often indicated as a critical life stage for interventions that are aimed at increasing well-being. Research has shown that many adolescents achieve positive outcomes, such as life satisfaction, despite the risks they are exposed to. These adolescents could be seen as resilient. Protective factors, such as strengths and coping, are considered important contributors to resilience. Continued research is needed to understand the process of resilience, especially for developing, multicultural countries such as South Africa. Thus, the aim of this study is to clarify the interrelationship between trauma exposure, strengths, coping, resilience and life satisfaction in South African adolescents. A non-experimental, correlational design was used for this purpose. A random sample of 1 073 Grade 8 learners from 10 Free State schools in both urban and rural areas was included in the study. The data were collected with standardised psychometric tests that were administered during school days under the supervision of registered psychologists. The measuring instruments, provided in English, Afrikaans and Sesotho, were a biographical questionnaire; a shortened version of the Stressful Live Events Screening Questionnaire (Goodman, Corcoran, Turner, Yuan, & Green, 1998); the Behavioural and Emotional Rating Scale (Epstein & Sharma, 1998); the Coping Schemas Inventory (Wong, Reker, & Peacock, 2006); the Resiliency Scales for Children and Adolescents (Prince-Embury, 2006); and the Satisfaction with Life Scale (Diener, Emmons, Larsen, & Griffin, 1985). The relations between the different variables were examined by means of Structural Equation Modelling (SEM). The results indicate that trauma exposure is prevalent among South African adolescents, with black adolescents being exposed more than white adolescents. Also, exposure to multiple traumatic events is common. The findings show that adolescents’ levels of resilience and life satisfaction are average, whereas black adolescents’ level of resilience was proven to be significantly lower than that of white adolescents. Significant correlations were found between most of the variables included in the study. This provides evidence for the interrelated nature of the variables, and confirms the complexity of the interaction between risk and protective factors in the resilience process. The model that hypothesises the direction of the relationships between the variables was a good fit for the group of black adolescents and a reasonable fit for the total group of participants. Trauma exposure decreases life satisfaction, resilience and strengths, while it increases emotional reactivity. The results highlight the vital role of strengths in the context of trauma exposure because all of the strengths measured in this study increased resilience and decreased emotional reactivity. Coping strategies were also shown to increase resilience. Increased resilience predicts increased life satisfaction and provides evidence that developing resilience in adolescents might contribute positively to their subjective well-being. Intervention is indicated especially for black adolescents because the results point to their being less resilient than white adolescents. The findings could be used to inform intervention programmes that are aimed at enhancing well-being in adolescents. In this regard, the findings indicate that a strength-based approach be followed and that adolescents’ range of coping skills be increased. Also, the need for psycho-education for adolescents is highlighted. Parents, schools and government institutions should not only be made aware of the significance of investing in adolescents, but should also be assisted to develop the skills needed to serve as role models and sources of support in developing adolescents’ resilience.

Die huidige Suid-Afrikaanse adolessent-kohort het in ŉ dekade van sosiopolitieke transformasie grootgeword. Hierdie tydperk het met onvermydelike en voortdurende onstabiliteit gepaardgegaan, veral in die ekonomiese, onderwys- en gesondheidstelsel. Suid-Afrikaners in die algemeen kom teen hoë vlakke van traumablootstelling te staan weens misdaad en geweld, gesinsontbinding, huishoudelike geweld, ongelukke, siekte en besering. Jong adolessente het egter nog met ontwikkelingsveranderinge in elke gebied van funksionering te kampe. Trouens, vroeë adolessensie word dikwels aangedui as ŉ kritieke lewensfase vir intervensie wat op die verhoging van welstand gemik is. Navorsing toon dat baie adolessente wel positiewe uitkomste soos lewenstevredenheid bereik ten spyte van die risiko’s waaraan hulle blootgestel word. Hierdie adolessente kan as veerkragtig gesien word. Beskermende faktore, soos sterkpunte en coping, word as belangrike bydraers tot veerkragtigheid beskou. Volgehoue navorsing is egter nodig om die proses van veerkragtigheid te verstaan, veral in ontwikkelende, multikulturele lande soos Suid-Afrika. Daarom is die doel van hierdie studie om die onderlinge verwantskap tussen traumablootstelling, sterkpunte, coping, veerkragtigheid en lewenstevredenheid in Suid-Afrikaanse adolessente uit te klaar. ŉ Nie-eksperimentele, korrelasionele ontwerp is vir dié doel gebruik. ŉ Ewekansige steekproef van 1 073 graad 8-leerders van 10 Vrystaatse skole in stedelike sowel as landelike gebiede is in die studie ingesluit. Die data is versamel met behulp van gestandaardiseerde psigometriese toetse wat gedurende skooldae onder toesig van geregistreerde sielkundiges afgeneem is. Die meetinstrumente is in Engels, Afrikaans en Sesotho beskikbaar gestel en was die volgende: ŉ biografiese vraelys; ŉ verkorte weergawe van die Stressful Live Events Screening Questionnaire (Goodman, Corcoran, Turner, Yuan, & Green, 1998); die Behavioural and Emotional Rating Scale (Epstein & Sharma, 1998); die Coping Schemas Inventory (Wong, Reker, & Peacock, 2006); die Resiliency Scales for Children and Adolescents (Prince-Embury, 2006); en die Satisfaction with Life Scale (Diener, Emmons, Larsen, & Griffin, 1985). Die verhoudings tussen die verskillende veranderlikes is deur middel van strukturele vergelykingsmodellering (SVM) ondersoek. Die resultate toon dat traumablootstelling algemeen onder Suid-Afrikaanse adolessente voorkom, met swart adolessente wat meer as wit adolessente blootgestel word. Blootstelling aan veelvoudige traumatiese gebeure is ook algemeen. Adolessente se vlakke van veerkragtigheid en lewenstevredenheid is gemiddeld, waar swart adolessente se vlak van veerkragtigheid beduidend laer as dié van wit adolessente toon. Beduidende korrelasies is tussen die meeste van die veranderlikes in die studie gevind. Dit lewer bewys van die onderling verwante aard van die veranderlikes en bevestig die kompleksiteit van die interaksie tussen risiko- en beskermende faktore in die veerkragtigheidsproses. Die model wat gebruik is om hipoteses oor die rigting van die verwantskappe tussen die veranderlikes te stel, is ŉ goeie passing vir die groep swart adolessente, en ŉ redelike passing vir die totale groep deelnemers. Traumablootstelling verlaag lewenstevredenheid, veerkragtigheid en sterkpunte, terwyl dit emosionele reaktiwiteit verhoog. Die belangrike rol van sterkpunte in die konteks van traumablootstelling is beklemtoon, aangesien al die sterkpunte wat in die studie gemeet is veerkragtigheid verhoog en emosionele reaktiwiteit verlaag. Coping-strategieë verhoog ook veerkragtigheid, volgens die resultate. Verhoogde veerkragtigheid voorspel verhoogde lewenstevredenheid, wat bewys dat die ontwikkeling van veerkragtigheid in adolessente positief tot hulle subjektiewe welstand kan bydra. Intervensie word aangedui veral vir swart adolessente, aangesien die bevindinge toon dat hulle minder veerkragtig as wit adolessente is. Die bevindinge kan aangewend word as basis vir intervensieprogramme wat op die bevordering van welstand in adolessente gemik is. ŉ Benadering wat op sterkpunte gegrond is en adolessente se reeks coping-vaardighede uitbrei, is ook aangedui. Die bevindinge wys verder op die behoefte aan psigo-opvoeding vir adolessente. Ouers, skole en staatsinstansies moet nie slegs bewus gemaak word van die belangrikheid om in adolessente te belê nie, maar moet ook bygestaan word om vaardighede te ontwikkel ten einde as rolmodelle en ondersteuningsbronne in die ontwikkeling van adolessente se veerkragtigheid te dien.
Thesis (Ph.D. (Psychology))--University of the Free State, 2014
Keywords: Resilience; Trauma exposure; Strengths; Coping; Life satisfaction; Adolescents; South Africa; Resilience (Personality trait) in adolescence; Adaptability (Psychology); Teenagers